Blocking Effects of Human Tau on Squid Giant Synapse Transmission and Its Prevention by T-817 MA - Moreno, Herman; Choi, Soonwook; Yu, Eunah; Brusco, Janaina; Avila, Jesus; Moreira, Jorge; Sugimori, Mutsuyuki; Llinas, Rodolfo R. (Frontiers in Synaptic Neuroscience, 2011)
Filamentous tau inclusions are hallmarks of Alzheimer’s disease (AD) and related neurodegenerative tauopathies, but the molecular mechanisms involved in tau mediated changes in neuronal function and their possible effects on synaptic transmission are unknown. We have evaluated the effects of human tau protein injected directly into the presynaptic terminal axon of the squid giant synapse, which affords functional, structural, and biochemical analysis of its action on the synaptic release process. Indeed, we have found that at physiological concentrations recombinant human tau isoforms (h-tau 42) become phosphorylated, produce a rapid synaptic transmission block, and induce the formation of clusters of aggregated synaptic vesicles in the vicinity of the active zone. Presynaptic voltage clamp recordings demonstrate that h-tau does not modify the presynaptic calcium current amplitude or kinetics. Analysis of synaptic noise at the post-synaptic axon following pre-synaptic h-tau42 microinjection revealed an initial phase of increase spontaneous transmitter release followed by a marked reduction in noise. Finally, systemic administration of T-817MA, a proposed neuro-protective agent, rescued tau-induced synaptic abnormalities. Our results show novel mechanisms of h-tau42 mediated synaptic transmission failure and more importantly identify a potential therapeutic agent to treat/prevent tau-related neurotoxicity.